Goodbye, Amanda the good - Shreve, Susan Richards (New York : Scholastic, 2001)
After three months as a nobody in junior high, Amanda finds her world changing when members of the popular and exclusive clique The Club set their sights on her for membership.
Keywords: Popularity -- Fiction; Clubs -- Fiction; Schools -- Fiction